Application of ISO 45001 in the improvement of Occupational Health and Safety Management within the framework of Law No. 29783 in metalworking companies - Hinostroza Jahuana, Carlos Enrique (2022)
The intention of this article is to explain how to efficiently apply the Occupational Health and Safety Management System within the framework of the International Standard ISO 45001: 2018 and Law No. 29783 in an metalworking company improves safety conditions and health of the company's collaborators and this favors achieving better working conditions, from this it is understood that every organization must have as its objective a Personnel Management, with humanity and tolerant and quality criteria. In this process it has been shown that the ISO 45001: 2018 standard is valuable and that value that it has been acquiring in organizations is with the benefit it has been acquiring in the organization of the company, in the study a diagnosis has been carried out that has been verified How non-compliance generates dissatisfaction and this causes problems in the management of occupational health and safety and if the opposite is the case, this improves, which much depends, in addition, on the efficient application of ISO 45001: 2018, with the help of analysis From the proposed situation, it has been shown that this situation is extremely satisfactory.